The Removal of Cured Urea-Formaldehyde Adhesive towards Sustainable Medium Density Fiberboard Production: A Review - Muhammad Adly Rahandi Lubis; Sumit Yadav Manohar; Raden Permana Budi Laksana; Widya Fatriasari; Maya Ismayati; Faizatul Falah; Nissa Nurfajrin Solihat; Fahriya Puspita Sari; Wahyu Hidayat (Jurnal Sylva Lestari, 2021)
Medium density fiberboard (MDF) is an engineered wood product that has density and specific gravity similar to solid wood, ranging from 600 to 800 kg/m3 of density and 0.6 to 0.8 of specific gravity. This makes MDF suitable to partially replace solid wood, particularly for interior application. Approximately over than 100 million m3 of MDF are produced in 2020, resulting in a large amount of waste MDF will be generated in the next 20 years. MDF is produced using urea-formaldehyde (UF) resins adhesive. UF resins adhesive is a poly-condensation product of urea and formaldehyde via an alkaline acid two-step reaction. Sustainable MDF production is required as the world is facing climate change and deforestation. Recycling is a way to support sustainable production in the engineered wood products manufacturing. Many attempts have been done to find ways to recycle waste MDF. The main problem is UF resins, which bond the MDF panel fibers. In order to re-manufacture the waste MDF into new recycled MDF, UF resins should be eliminated from the waste MDF before being used. The presence of UF resins in MDF can interfere with the utilization of the recycled fibers, whether it will be used as a raw material for new MDF or other composite products. This paper reviews the process of removal of cured UF resins from waste MDF panel by considering the hydrolytic stability of cured UF resins for MDF recycling, providing a comprehensive review of how cured UF resins can be removed from waste MDF and characterization of recycled fibers obtained from recycling prior to re-manufacturing of recycled MDF panel.